Unsur Intrinsik Cerita Pendek “Ana Al-Maut” Karya Taufiq El-Hakim - Mushokhikhul Khasanah (Jurnal Multidisiplin Madani, 2022)
Literary work, is a creation of the author, which in itself has an autonomous structure that can be understood as a unified whole. Therefore, to understand its meaning, a literary work must be studied based on its own structure. Things that are extrinsic such as writers, readers, or socio-cultural environments must be ruled out, because they do not have a direct relationship with the structure of the literary work. In this study, the researcher tries to discuss one of the short stories by Dr. Taufik el-Hakim, entitled Ana Al-Maut which is contained in his anthology of short stories entitled Arinillaha. This research uses Robert Stanton's structural analysis. The main basis for this analysis is the work itself, as well as the building blocks of its structure. In works of fiction, the building blocks of the structure consist of story facts, themes and story tools. The facts of the story consist of characters, plot and setting. The means of the story are the title, point of view, style and tone, irony and so on. After analyzing, the researcher found a harmonious integration between form and content in the work, so that this work has a beautiful value and high quality.